FPGA innovation research in the Netherlands: present landscape and future outlook - Alachiotis, Nikolaos; van den Belt, Sjoerd; van der Vlugt, Steven; van der Walle, Reinier; Safari, Mohsen; Endres Forlin, Bruno; De Matteis, Tiziano; Al-Ars, Zaid; Jordans, Roel; Sousa de Almeida, António J.; Corradi, Federico; Baaij, Christiaan; et al. (Frontiers in High Performance Computing, 2025)
Field programmable gate arrays (FPGA) have transformed digital design by enabling versatile and customizable solutions that balance performance and power efficiency, yielding them essential for today's diverse computing challenges. Research in the Netherlands in both academia and industry plays a major role in developing new innovative FPGA solutions. This survey presents the current landscape of FPGA innovation research in the Netherlands by delving into ongoing projects, advancements, and breakthroughs in the field. Focusing on recent research outcome (within the past 5 years), we have identified five key research areas: (a) FPGA architecture, (b) FPGA robustness, (c) data center infrastructure and high-performance computing, (d) programming models and tools, and (e) applications. This survey provides in-depth insights beyond a mere snapshot of the current innovation research landscape by highlighting future research directions within each key area; these insights can serve as a foundational resource to inform potential national-level investments in FPGA technology.